Synchronization of chaotic optomechanical system with plasmonic cavity for secured quantum communication - Mulubirhan Dangish; Abebe Belay Gemta; Alemayehu Getahun Kumela; Umer Sherefedin; Ruth Birhanu (AIP Advances, 2025)
Cavity optomechanical systems generate, manipulate, and detect quantum states of light by exploiting the intricate interplay between light confined to optical cavities and mechanical vibrations. However, these systems can be subjected to thermal noise due to the inherent thermal vibrations of the mechanical components, introducing fluctuations that can obscure the delicate quantum states and dynamics of the system. Therefore, in this study, we present a theoretical analysis of the synchronization dynamics in chaotic optomechanical systems comprising two cavity modes: one strongly influenced by a localized surface plasmon field and another exhibiting minimal influence. We investigated the energy transfer efficiency of silicon divacancies, gallium arsenide, and indium phosphide by analyzing their absorption and extinction cross sections. The results indicate that gallium arsenide surpasses both silicon divacancies and indium phosphide in performance. Employing the Hamiltonian notation, we calculated the effect of optical force and damping rates on the optomechanical system over time. In addition, using Lyapunov chaotic attractors, we demonstrated that the localized surface plasmons significantly boost the strength of the electromagnetic field within the strongly influenced cavity mode and effectively synchronize the two modes through a coherent phase relationship with minimal error. Further, we exploited the initial chaotic behavior for quantum key generation, showcasing the system’s potential for efficient and secure quantum communication within a time frame of 0.7 μs. Our findings pave the way for enhanced coherence and reliability in secure quantum communication systems, thus contributing to the advancement of this rapidly evolving field.